Towards software-based tools for business model development: Using external stimuli for business model idea generation - Szopinski, Daniel (Bosch Business Model Innovation Summit 2018)

Patterns of Store-oriented Software Ecosystems: Detection, Classification, and Analysis of Design Options - Jazayeri, Bahar; Zimmermann, Olaf; Küster, Jochen; Engels, Gregor; Kundisch, Dennis; Szopinski, Daniel (The Latin American Conference on Pattern Languages of Programs (SLPLoP))
Software companies nowadays create ecosystems of users and third-party providers around their platforms. They often provide online stores so that the third-party developments can be exposed to users directly. The resulting ecosystems differ significantly from each other in their architectural designs because their providers differ in terms of business goals and contexts. Until now, this architectural diversity and rationale behind it are not well-understood. Therefore, it is not clear which software features contribute to ecosystem’s success with respect to certain business goals and context. This hinders systematic creation of ecosystems in the future. Thus, decision-making becomes too risky; for future ecosystem providers, which may lead to creation of inefficient ecosystems that lack critical features, and for third-party providers to rely on ad-hoc choices while deciding on suitability of an ecosystem for their future career. In this paper, we introduce three design patterns for store- oriented software ecosystems by classifying the design decisions, business goals, and context of 111 store-oriented software ecosystems. Each design pattern provides an architectural solution to achieve a different business goal while supporting a different context. We discuss how the design patterns are applied together in order to achieve more business goals. Our work supports ecosystem and third-party providers by sharing practice-proven architectural solutions, helping them to take informed architectural decisions and reduce technical risks.

Towards explaining the popularity of the Business Model Canvas: A dual coding approach - John, Thomas; Szopinski, Daniel (Proceedings of the Multikonferenz Wirtschaftsinformatik 2018 (MKWI), Lüneburg, Germany)

Platform Launch Strategies - Stummer, Christian; Kundisch, Dennis; Decker, Reinhold (Business & Information Systems Engineering)

Evaluation von Taxonomien: Ein Literaturüberblick - Hoffmeister, Jiajia

Zweiseitige Märkte und Plattformökonomie in der Information Systems-Forschung - Ein klassifizierender Literaturüberblick - Valentin, Andreas

Das Konzept der Kreativität in der Wirtschaftsinformatik: Ein Literaturüberblick - Weigang, Jana

How Software Can Support Innovating Business Models: A Taxonomy of Functions of Business Model Development Tools - Szopinski, Daniel; Schoormann, Thorsten; John, Thomas; Knackstedt, Ralf; Kundisch, Dennis (Proceedings of the 23rd Americas Conference on Information Systems (AMCIS))
The interest in business model innovation has risen rapidly in recent years, and software tools for business model development hold great promise for supporting business model innovation. Nonetheless, virtually no design-relevant knowledge exists concerning the functions that such tools should possess. Therefore, we develop a comprehensive taxonomy that identifies characteristic functions of software-based business model development tools. For developing the taxonomy, we draw on prior research on business model innovation, process modeling, and creativity support systems, and we analyze software tools for business model development that have been proposed in practice. The resulting taxonomy can support practitioners in their tool (re-)design and investment decisions, and for researchers can serve as a preliminary step towards more advanced theories for software tools for business model development.

How Software Can Support Innovating Business Models: A Taxonomy of Functions of Business Model Development Tools - Szopinski, Daniel; Schoormann, Thorsten; John, Thomas; Knackstedt, Ralf; Kundisch, Dennis (Bosch Business Model Innovation Summit 2017)

Geschäftsmodelle elektronischer Handelsplattformen - Martens, Martin

Geschäftsmodell-Modellierungssprache/Business Model Modeling Language - Kundisch, Dennis; John, Thomas (Enzyklopädie der Wirtschaftsinformatik, GITO)

On-The-Fly Computing: Ein Referenzmodell für individualisierte IT-Dienstleistungen in dynamischen Märkten - Szopinski, Daniel; Jazayeri, Bahar; Engels, Gregor; Kundisch, Dennis (Proceedings of the Workshop Enterprise Architecture Management in Forschung und Praxis, INFORMATIK 2017, Chemnitz, Germany)
Das Enterprise Architecture Management stellt umfangreiche Methoden, Modelle und Frameworks für die Modellierung von Unternehmensarchitekturen zur Verfügung. Die Entwicklung von Software und deren Integration in IT-Landschaften ist heutzutage zunehmend von Komplexität und Unsicherheit geprägt. Dieser Beitrag (Research-in-progress) möchte ein neues Paradigma – das „On-The-Fly Computing“ – vorschlagen, um diesen Herausforderungen zu begegnen, mögliche Lösungsansätze zu diskutieren sowie erste Ergebnisse eines Referenzmodells für individualisierte IT-Dienstleistungen in dynamischen Software-Märkten dokumentieren.

On-The-Fly Computing Meets IoT Markets - Towards a Reference Architecture - Jazayeri, Bahar; Schwichtenberg, Simon (Proceedings of the International Conference on Software Architecture (ICSA) IoT-ASAP Workshop)
The Internet of Things (IoT) connects the things of our everyday life and supports usin our common activities.Several markets for IoT services have been created. These markets enable IoT users to search and compose services in order to support an IoT activity.However, existing IoT markets like IFTTT (If This Then That) are not convenient for users with respect to service discovery and composition.The objective of On-the-fly (OTF) computing is to configure and provide software markets that fulfill individual users' wishes by the automatic on-the-fly composition of single services.The architecture framework of On-the-fly computing markets helps architects to systematically develop these systems in different domains.In this paper, we use our OTF architectural framework to examine the requirements of a reference architecture for IoT markets.Furthermore, we perform a comparison between the architecture of IFTTT as an existing IoT market with this reference architecture. The results show how existing IoT markets can be improved. In return, the practical knowledge of IFTTT is taken to the reference architecture.This knowledge helps to overcome the limitations of today's IoT markets or creating new markets in the future.

On the Necessity of an Architecture Framework for On-The-Fly Computing - Jazayeri, Bahar; Schwichtenberg, Simon (Proceedings of Softwaretechnik-Trends Workshops)

Visual Languages for Modeling Business Models: A Critical Review and Future Research Directions - John, Thomas; Kundisch, Dennis; Szopinski, Daniel (Proceedings of the 38th International Conference on Information Systems (ICIS), Seoul, South Korea)
A multiplicity of visual languages have been proposed for representing business models. These languages are claimed to facilitate tasks such as understanding, communicating, and innovating a business model; and have been developed rather independently by scholars from accounting, computer science, information systems, and strategy. Consequently, the existing approaches greatly differ and to some extent contradict each other, for example, regarding their understanding of the business model concept, their terminology, and their visual notations – which means there is little common ground for developing a cumulative stream of research. Therefore, we provide a systematic, cross-disciplinary review of this emerging field and synthesize the pragmatic, semantic, and syntactic foundations of the proposed approaches. Further, we derive an agenda for future research and discuss the challenges that lie ahead to advance the field.

Literaturüberblick über die Rolle von Business Architecture in Enterprise Architecture - Lohrsträter, Lukas

Geschäftsmodell-Frameworks zur Analyse und Klassifikation bestehender Geschäftsmodelle - Warkentin, Markus

Towards Explaining the Popularity of the Business Model Canvas: A Dual-coding Approach - John, Thomas; Szopinski, Daniel (1st Business Model Conference)

Supporting Business Model Idea Generation Through Machine-generated Ideas: A Design Theory - John, Thomas (1st Business Model Conference)

A Variability Model for Store-oriented Software Ecosystems: An Enterprise Perspective (Supplementary Material) - Jazayeri, Bahar; Zimmermann, Olaf; Engels, Gregor; Kundisch, Dennis